NOVEL APPLICATION OF BIO SORBENTS FOR REMOVAL OF CRUDE OIL FROM SEAWATER - ASADPOUR, ROBABEH (2017)
Oil spills from tanker or oil well have detrimental effects on environment and economy. Clean up of spilled oil is difficult and costly. Therefore there is a need for removal of oil from water. Methods dealing with oil spill are mechanical extraction, in situ burning, use of dispersants, and bioremediation. These methods have failed to ensure environmental safety, ecosystem integrity, and lead to environmental hazards. Gravity separator as another method to separate oil and water in the tank does not recover small oil droplets. One of the most economical and efficient methods for oil spill cleanup is mechanical extraction by sorbents. The aim of this study was to investigate the efficiency of different local organic materials for removal of Tapis and Arabian crude oil from seawater. In this study raw and modified organic agricultural wastes, as low-cost adsorbents were used for oil spill cleanup in an aquatic environment. Mangrove bark, corn silk, and oil palm empty fruit bunch (OPEFB) fiber were selected as sorbents. The properties of the sorbents were modified using fatty acids and acetic anhydride to enhance their sorption capacity. Results showed that acetylated sorbents have higher sorption capacity than raw one with 4.27, 16.68, and 6.8 g/g for mangrove bark, corn silk, and OPEFB fiber, respectively. The highest sorption capacity was achieved at optimum pH of 8, 7, and 8, at a temperature of 25 to 30 °C (for Tapis crude oil) and 35 to 40 °C (for Arabian crude oil), and contact time of 25 to 30 min. The result of reusability of sorbents showed that corn silk and OPEFB fiber can be reused up to five cycles. The rate of oil sorption onto the sorbents was described by Pseudo-second-order models for corn silk and OPEFB fiber, but this model was not described well for adsorption of crude oil onto the mangrove bark due to the predicted qe and lower R2. Based on the fitting of the experimental data, Freundlich model was more acceptable for corn silk while Langmuir model was better described for mangrove bark and OPEFB fiber regarding the closely of qm and qe experimental and highest R2. Application of the acetylated corn silk could reduce the oil concentration in the oil/water separator by 73.40 %.